2008
DOI: 10.1016/j.pupt.2007.07.002
|View full text |Cite
|
Sign up to set email alerts
|

The safety and effects of the beta-blocker, nadolol, in mild asthma: An open-label pilot study

Abstract: Beta-blockers are currently contraindicated in asthma because their acute administration may be associated with worsening bronchospasm. However, their effects and safety with their chronic administration are not well evaluated. The rationale for this pilot study was based on the paradigm shift that was observed with the use of beta-blockers in congestive heart failure, which once contraindicated because of their acute detrimental effects, have now been shown to reduce mortality with their chronic use. We hypot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
92
0
5

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 120 publications
(105 citation statements)
references
References 51 publications
8
92
0
5
Order By: Relevance
“…2) and similar to what we have observed with chronic administration of inverse agonists in antigen-driven models of asthma by using other mouse strains (15). Although future investigations are still needed to investigate the relevance of these findings in human asthma, a recent study demonstrated a dose-dependent attenuation of AHR with 9-week administration of oral nadolol in patients with mild asthma (26).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…2) and similar to what we have observed with chronic administration of inverse agonists in antigen-driven models of asthma by using other mouse strains (15). Although future investigations are still needed to investigate the relevance of these findings in human asthma, a recent study demonstrated a dose-dependent attenuation of AHR with 9-week administration of oral nadolol in patients with mild asthma (26).…”
Section: Discussionsupporting
confidence: 79%
“…Based on the paradigm shift that occurred in chronic CHF therapy, we investigated whether chronic treatment with ␤ 2 -AR inverse agonists, a class of drugs currently contraindicated in asthma because of their potential to produce acute bronchoconstriction, may be beneficial with long-term administration (14,15,25,26). Indeed, we found that chronic treatment with ␤ 2 -AR inverse agonists produced a time-dependent decrease in AHR and mucous metaplasia in a murine model of asthma (14,15), whereas treatment with alprenolol, a ␤-blocker without inverse agonist properties, did not decrease AHR (15).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, after encouraging results in murine studies, the first proof-ofconcept open-label study in humans was set to evaluate the safety and effect of ß-blockers for the potential treatment of asthma. It showed that chronic dose-escalating non-selective ß-blocker nadolol use in patients with steroid-naive mild asthma was not only safe but could have beneficial effects on airway hyperresponsiveness [4]. Indeed, in eight out of the ten subjects evaluated, nine weeks of beta-blocker treatment produced a significant, dose-dependent increase in the methacholine PC20.…”
mentioning
confidence: 99%
“…Whether treatment of asthmatics with ␤ 2 AR inverse agonists results in a brief period of adverse effects followed by improved asthma control remains to be determined. A recent pilot study examining nadolol effects in 10 mild asthmatics reported 4 subjects as experiencing a moderate drop in expired airflow after their first dose of nadolol (9). However, after 9 weeks of treatment, mean values for expired airflow were greater than those measured at baseline, and a significant reduction in the sensitivity to the bronchoconstricting agent methacholine was observed.…”
mentioning
confidence: 99%